Applied engineering sciences : proceedings of the AASRI International Conference on Applied Engineering Science, Hollywood, USA, 23-24 July 2014 - Deng, Wei (Of the American Applied Sciences Research Institute) (Advances in engineering & applied science, 2015)
This proceedings volume contains selected papers presented at the 2014 AASRI International Conference on Applied Engineering Sciences, held in Hollywood, LA, USA. Contributions cover the latest developments and advances in the field of Applied Engineering Sciences.